The COVID‐19 pandemic: considerations for resuming normal colorectal services. (28th August 2020) - Pellino, G.; Vaizey, C. J.; Maeda, Y.; ,
Abstract: This European Society of Coloproctology guidance focuses on a proposed conceptual framework to resume standard service in colorectal surgery. The proposed conceptual framework is a schematic and stepwise approach including: in‐depth assessment of damage to non‐COVID‐19‐related colorectal service; the return of service (integration with the COVID‐19‐specific service and the existing operational continuity planning); safety arrangements in parallel with minimizing downtime; the required support for staff and patients; the aftermath of the pandemic and continued strategic planning. This will be dynamic guidance with ongoing updates using critical appraisal of emerging evidence. We will welcome input from all stakeholders (statutory organizations, healthcare professionals, public and patients). Any new questions, new data and discussion are welcome via https://www.escp.eu.com/guidelines .